2020
DOI: 10.3390/nu12123850
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-Containing Energy Shots Cause Acute Impaired Glucoregulation in Adolescents

Abstract: Caffeine-containing, nutritionally fortified energy shots are consumed at high rates by adolescents, yet little is known about their metabolic impact. The purpose of this study was to examine the consequences of small format, caffeinated energy shots on glucose metabolism and gastrointestinal hormone secretion in adolescents. Twenty participants aged 13–19 years participated in a double-blind, randomized cross-over study consisting of two trials separated by 1–4 weeks. Participants consumed a volume-matched ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…However, the presence of young subjects and the two-year period of observation seem to be inadequate to develop such metabolic disorders. On the contrary, Shearer et al [ 70 ] presented that caffeinated beverages could cause acute, transient insulin resistance in healthy adolescents. Moreover, ED consumers were also more likely to consume highly energy-dense fast foods and spend more than 6 h in front of a screen, which may result in an increased risk of being overweight or obese among adolescents [ 71 ].…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
“…However, the presence of young subjects and the two-year period of observation seem to be inadequate to develop such metabolic disorders. On the contrary, Shearer et al [ 70 ] presented that caffeinated beverages could cause acute, transient insulin resistance in healthy adolescents. Moreover, ED consumers were also more likely to consume highly energy-dense fast foods and spend more than 6 h in front of a screen, which may result in an increased risk of being overweight or obese among adolescents [ 71 ].…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
“…To date, no other studies have explored the influence of ED on glycemic control in adolescents. One study found impaired glucoregulation, characterized by hyperinsulinemia, in healthy adolescents after consuming energy shots [24]. Yet, it must be emphasized that EDs and energy shots are distinctly different.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine also inhibits the actions of adenosine leading to a rise in neurotransmitters, such as epinephrine and activation of the sympathetic nervous system causing pupil dilation, which brings about an increase in spherical aberration and retinal illumination changes. 24 Additives, such as guarana, further increase the caffeine content of energy drinks, 12 and there are also large amounts of various sugars present in energy drinks, which can lead to increased plasma glucose concentrations 25 and visual changes. Subsequently, Abokyi et al 14 identified the need for further studies on vision itself, highlighting that pupil size and accommodation are not the only determinants in retinal image formation.…”
Section: Introductionmentioning
confidence: 99%